Supplementation of Crataegi fructus alleviates functional dyspepsia and restores gut microbiota in mice - Hao, Liyu; Yu, Zeyue; Sun, Jianhui; Li, Zongyuan; Li, Jianliang; Deng, Yurong; Huang, Hanhui; Huo, Hairu; Li, Hongmei; Huang, Luqi (Frontiers in Nutrition, 2024)
Introduction Functional dyspepsia (FD), also known as non-ulcerative dyspepsia, is a common digestive system disorder. Methods In this study, an FD model was established using hunger and satiety disorders combined with an intraperitoneal injection of L-arginine. Indices used to evaluate the efficacy of hawthorn in FD mice include small intestinal propulsion rate, gastric residual rate, general condition, food intake, amount of drinking water, gastric histopathological examination, and serum nitric oxide (NO) and gastrin levels. Based on the intestinal flora and their metabolites, short-chain fatty acids (SCFAs), the mechanism of action of Crataegi Fructus (hawthorn) on FD was studied. The fecal microbiota transplantation test was used to verify whether hawthorn altered the structure of the intestinal flora. Results The results showed that hawthorn improved FD by significantly reducing the gastric residual rate, increasing the intestinal propulsion rate, the intake of food and drinking water, and the levels of gastrointestinal hormones. Simultaneously, hawthorn elevated substance P and 5-hydroxytryptamine expression in the duodenum, reduced serum NO levels, and increased vasoactive intestinal peptide expression in the duodenum. Notably, hawthorn increased the abundance of beneficial bacteria and SCFA-producing bacteria in the intestines of FD mice, decreased the abundance of conditional pathogenic bacteria, and significantly increased the SCFA content in feces. Discussion The mechanism by which hawthorn improves FD may be related to the regulation of intestinal flora structure and the production of SCFAs.